2024
DOI: 10.3389/fonc.2023.1310471
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis, treatment, and prognosis of stage IB non-small cell lung cancer with visceral pleural invasion

Zegang Ruan,
Xin Zhuo,
Chenyang Xu

Abstract: With the increasing implementation of early lung cancer screening and the increasing emphasis on physical examinations, the early-stage lung cancer detection rate continues to rise. Visceral pleural invasion (VPI), which denotes the tumor’s breach of the elastic layer or reaching the surface of the visceral pleura, stands as a pivotal factor that impacts the prognosis of patients with non-small cell lung cancer (NSCLC) and directly influences the pathological staging of early-stage cases. According to the late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 112 publications
0
0
0
Order By: Relevance
“…Therefore, early screening and diagnosis are a way to reduce mortality ( 3 ). Research has shown that combining genomics and genetics screening can improve the survival rate for lung cancer patients ( 4 - 6 ). Blood is the easiest source to obtain to acquire information about lung cancer ( 7 ), including circulating DNA and RNA ( 8 ), circulating tumor cells ( 9 ), serum metabolites ( 10 ), and lipids ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, early screening and diagnosis are a way to reduce mortality ( 3 ). Research has shown that combining genomics and genetics screening can improve the survival rate for lung cancer patients ( 4 - 6 ). Blood is the easiest source to obtain to acquire information about lung cancer ( 7 ), including circulating DNA and RNA ( 8 ), circulating tumor cells ( 9 ), serum metabolites ( 10 ), and lipids ( 11 ).…”
Section: Introductionmentioning
confidence: 99%